ANALISIS KESESUAIAN LULUSAN DKV STRATA SATU DENGAN BIDANG PEKERJAAN - R.A. Dita Saraswati; Galang Dwiki Setiadi (Serat Rupa: Journal of Design, 2020)
The current industrial revolution 4.0 has a significant impact on the profession of Visual Communication Designers, this is indicated by a large number of expertise in the field of DKV (Desain Komunikasi Visual in Indonesian) needed by various types of businesses along with the development of digital media technology. Jobs that can be entered by majors are also very diverse. This development in the DKV industry needs to be addressed by reviewing the number of graduates with suitable employment and how many graduates work in the appropriate field. Through this research, the relevance of graduates and the world of work will be examined as well as conducting an in-depth study of what specific skills must be possessed by DKV Maranatha graduates to be ready to enter the workforce. The method used in this research is a descriptive analysis method of survey type and case studies on students who graduated in 2016 and 2017. Through this study will also obtain an overview of the waiting time of graduates and the number of graduates working in the appropriate fields. This research will be able to complete the tracer study data and information for DKV Maranatha Program in developing and evaluating the curriculum.